Borneomyia, a new genus and two new species of Milichiidae (Diptera, Schizophora) - Brake, Irina (Zootaxa, 2004)
Borneomyia n. gen. and its two new species, B. tigra n. sp. and B. acanthophora n. sp. (Diptera, Milichiidae), are described from Borneo and nearby regions. The new genus belongs to the Phyllomyzinae and is characterized by a femoral organ on the male midfemur, by several ventral rows of 3-5 setulae on the basitarsomere of the hindleg, and by the brown spot, each, on the otherwise yellow antennal grooves.